INDIA VIX: Examining the Negative and Asymmetric Volatility Index – Market Return Relationship - Dhanaiah, Gangineni; Raghunatha Reddy, D.; Prasad, T. N. L. (Indian Journal of Finance, 2012)
This paper examines the behavior of India Volatility Index (India VIX). The researchers examined two aspects: First, the negative correlation between changes in India VIX and market returns. Second, the asymmetric nature of the changes in India VIX with respect to market returns. S&P CNX NIFTY Index has been used as a proxy for the market and the study period covers the period from March 2009 through November 2011. Using OLS Regression method on daily data, this study finds an inverse relation between movements in India VIX and movements in the NIFTY. The study reveals the asymmetric nature of the Volatility Index- Market Return relationship. This study is useful for understanding the behavior of India VIX and helps policymakers in the design of appropriate instruments based on India VIX for hedging and risk management.